Kelas Menulis Cahaya: Program Komunitas Literasi Berbasis Inovasi, Riset, dan Teknologi untuk Menjawab Tantangan Pendidikan - Ika Cahya Adiebia; Hamdani Hamdani; Liana Rochmatul Wachidah (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
There are problems in education in Indonesia, especially in Pamekasan, which urgently need to be resolved immediately in order to create a generation that is qualified and ready to face current developments. The aim of this research is to describe a literacy community program based on innovation, research and technology in the form of the Kelas Menulis Cahaya (KMC) as a solution to answer educational challenges in Pamekasan district. The Kelas Menulis Cahaya is one of the annual programs of the Pamekasan branch of the Forum Lingkar Pena (FLP) in collaboration with the Taman Baca Masyarakat (TBM) Maos. FLP is a structured, systematic and global literacy community with branches in Indonesia and abroad. Meanwhile, TBM Maos is a literacy community in Pamekasan district. This research uses a qualitative approach with a descriptive type. Data was obtained through observation, literature study, and interview transcripts. Based on this research, the Kelas Menulis Cahaya (KMC) program, based on innovation, research and technology, is considered capable of being a solution to educational problems in Pamekasan district, as well as producing a quality generation. The results of this research are that the writing class program in the Light Writing Light Class (KMC) program consists of several activity programs where the target of the program is to face the challenges of the times, namely the target of being able to read, liking reading, interest in reading, and reading culture.